Desenvolvimento de uma unidade laboratorial para quantificação de BTX como poluentes atmosféricos, usando microextração em fase sólida - Queiroz, Bruna Cibelle de (2011)
This dissertation aims the development of an experimental device to determine quantitatively the content of benzene, toluene and xylenes (BTX) in the atmosphere. BTX are extremely volatile solvents, and therefore play an important role in atmospheric chemistry, being precursors in the tropospheric ozone formation. In this work a BTX new standard gas was produced in nitrogen for stagnant systems. The aim of this dissertation is to develop a new method, simple and cheaper, to quantify and monitor BTX in air using solid phase microextraction/ gas chromatography/mass spectrometry (SPME/CG/MS). The features of the calibration method proposed are presented in this dissertation. SPME sampling was carried out under non-equilibrium conditions using a Carboxen/PDMS fiber exposed for 10 min standard gas mixtures. It is observed that the main parameters that affect the extraction process are sampling time and concentration. The results of the BTX multicomponent system studied have shown a linear and a nonlinear range. In the non-linear range, it is remarkable the effect of competition by selective adsorption with the following affinity order p-xylene > toluene > benzene. This behavior represents a limitation of the method, however being in accordance with the literature. Furthermore, this behavior does not prevent the application of the technique out of the non-linear region to quantify the BTX contents in the atmosphere.